Diastolic Dysfunction and Severity of Cirrhosis in Nonalcoholic Cirrhotic Patients - A. Salari; A. Shafaghi; M. Ofoghi; A. Saeidinia; F. Mansour-Ghanaei (International Journal of Hepatology)
Background. In this study, we evaluated the association between diastolic dysfunction severity and severity of cirrhosis in nonalcoholic cirrhotic patients. Methods. This cross-sectional study was conducted on all nonalcoholic cirrhotic patients who were admitted in Rasht Razi hospital the Cancer of Guilan Province, north of Iran, from January 2011 to March 2012. Severity of cirrhosis was evaluated by Child-Pugh score. A 12-lead surface ECG and echocardiographic studies were performed. We used a HDI 3000 (Philips ATL, Bothell, WA, USA) equipped with 2 to 4 MHz probes. Diastolic function was determined by an expert cardiac sonographer. Data were analyzed by SPSS for win (version16). A P value less than 0.05 was considered significant. Results. Sixty-tree percent of patients were male. The mean age of patients was 52.78±15.2 years. 22%, 38%, and 40% of patients were considered as child class A, B, and C, respectively. There was a significant relation between diastolic dysfunction and disease duration (P=0.001), female gender (P=0.004), age > 60 years (P=0.045), and severity of cirrhosis (P=0.048). On multivariate analysis, decreased E/A ratio (P=0.03) and disease duration (P=0.02) showed an independent significant relation. Conclusion. According to the relation between severity of cirrhosis and diastolic dysfunction, we recommend cardiac assessment in all child B and C cirrhotic patients.